Adequacy of Technological-Pedagogical Preparations of General High Schools in the K To 12 Curriculum: A Comprehensive Mapping - Gomez, Aurelio Jr, S.; Macariola, Julie Simon (PPSDP International Journal of Education, 2025)
This study determined the adequacy of technological-pedagogical preparation of general high schools of Digos City Division and Davao del Sur Division in the K to 12 Curriculum. This utilized the descriptive survey to explore the perceived barriers that teachers in Grades 7 and 8 encounter on the readiness of the general high schools in implementing the K to 12 Curriculum. Comprehensive mapping was made to measure the technological and pedagogical preparedness. There were 55 teacher respondents from two school divisions of Davao del Sur and Digos City who served as participants of the study. Mean, frequency, and analysis of variance were employed in the analysis of the data gathered. It was found out that the technological-pedagogical preparations of general high schools in the K to 12 Curriculum is highly adequate. Three of the four indicators were found to be highly adequate, namely: equipment and facilities, vertical articulation of teachers and framework orientation. The other indicator, shop layout, was found to be moderately adequate. There was no significant difference on the degree of adequacy of technological-pedagogical preparations of general high schools in the K to 12 Curriculum. The findings captured the insights and experiences of the teachers, which were essential in determining exactly what general high schools lack in terms of technology and pedagogical preparedness. The study recommends that the DepEd and TESDA Officials should collaborate with school administrators in the inspections of schools in terms of building equipment and facilities.